KARAKTER ORANG MADURA DAN FALSAFAH POLITIK LOKAL - Hidayat, Ainurrahman (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Abstrac This article attempts to explore the basic character of Madurese people that put the moral-ethic basics on every attitude, utterances, and behavior of Madurese local politic phenomena. The study results four basic characteristics of Madurese---ejhin, koko, gherra and saduhunah. Those become local wisdom of Madurese people. The four basic characters should have introduced and provided each Madurese local politic phenomena to reach a better politic life. Ejhin character carries a tolerant nature, friendship and dependent.Â  Koko character introduces loyality, consistency, trust and responsibility. Gherra character reflects carefulness, transparency, and fairness. Saduhunah describes honesty and innocent. Kata-kata kunci ejhin, gherra, koko, saduhuna